2002
DOI: 10.1111/j.1346-8138.2002.tb00219.x
|View full text |Cite
|
Sign up to set email alerts
|

Patch Testing in Discoid Eczema

Abstract: Fifty patients of both sexes with clinically suspected discoid eczema were patch tested with the Indian Standard Patch Test Battery approved by the Contact and Occupational Dermatosis Forum of India (CODFI). Most of these patients were young adults between 20 and 39 years old, with a mean age of 36 years. The mean duration of symptoms was 21/2 years. The occupational profiles of the patients included farmers (24%), housewives (18%), students (14%), housewives engaged in farming (12%), shopkeepers (10%), and la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 10 publications
(15 reference statements)
0
8
0
Order By: Relevance
“…In a series of 4825 patients, patch-tested by 10 dermatologists in 7 European countries, 100 subjects (2.1%) had nummular dermatitis, and 17% of these had relevant positive reactions. 23 Others have reported variable incidence of contact allergy in nummular eczema, ranging from 30.1%, 24 40.6%, 27 50%, 25,26 up to 77.9%. 39 Regardless of such variability from one case series to another, likely a bias from different cohorts numbers, the above data suggest that contact allergy is common in persistent discoid eczema.…”
Section: Contact Allergymentioning
confidence: 97%
“…In a series of 4825 patients, patch-tested by 10 dermatologists in 7 European countries, 100 subjects (2.1%) had nummular dermatitis, and 17% of these had relevant positive reactions. 23 Others have reported variable incidence of contact allergy in nummular eczema, ranging from 30.1%, 24 40.6%, 27 50%, 25,26 up to 77.9%. 39 Regardless of such variability from one case series to another, likely a bias from different cohorts numbers, the above data suggest that contact allergy is common in persistent discoid eczema.…”
Section: Contact Allergymentioning
confidence: 97%
“…A high percentage of these showed clinically‐relevant positive patch tests with rubber, chemicals and metals as the common allergens 67 . In an Indian study on 50 patients with discoid eczema, patch testing analysis showed a positive reaction to allergens in 56%, with potassium dichromate as the most common allergen (20%), followed by nickel (16%), cobalt chloride and fragrances (12% each) 68 . Discoid eczema may be recognized in three different patterns: (i) hands and forearms; (ii) limbs and trunk; and (iii) dry discoid eczema.…”
Section: Clinical Classificationmentioning
confidence: 99%
“…19 Potassium dichromate was the most common allergen (20%), followed by nickel (16%), cobalt chloride and fragrance mix (12% each) in decreasing order of frequency.…”
mentioning
confidence: 96%
“…20% and 16% respectively; whereas in our series five (12.5%) patients were sensitive to nickel. 19 Allergy to components of topical preparations is common in patients suffering from chronic dermatitis. Pasricha et al reported contact sensitivity to neomycin in 28% of their patients of suspected medicament contact dermatitis.…”
mentioning
confidence: 99%